(untitled) (Annals of Medical Research, 2021)
Aim: Health care workers especially dentists are at risk due to the fact that they are in direct contact with the blood and body fluids. In the present study, it was aimed to determine the preoperative seropositivity of HBsAG, anti-HBs, anti-HCV, and anti-HIV in the patients undergoing dental surgical procedure under local anesthesia.Material and Methods: 1598 patients who were admitted to Department of Oral and Maxillofacial Surgery between 2017-2018 and underwent surgical intervention for various reasons were included. Demographic data and serum samples taken preoperatively from patients were retrospectively evaluated in terms of HBsAg, Anti-HBs, Anti-HCV and Anti-HIV seropositivity by using archive records. Furthermore, the vocational and educational status of the HBsAg (+) patients in addition their awareness about hepatitis were investigated.Results: Of the 1598 patients, 591 (37%) were males; 1007 (63%) were females. The total number of patients with HBV carriers was 73 (4.6%), the number of anti-HBs-positive patients was 828 (51.8%), and the number of anti-HCV-positive patients was 3 (0.19%). Anti-HIV positivity has been observed in none of the patients. When evaluated according to the age ranges, HBsAg was mostly detected positive in the age ranges of 21-30 and 30-40; when evaluated according to sex, HBsAg was detected higher in women.Conclusions: Knowing the prevalence of infectious diseases is highly important for both the prevention and early diagnosis of these diseases. Besides, knowing the seropositivity of these diseases before surgical interventions will facilitate for both oral and maxillofacial surgeons and other health care personnel to take necessary safety precautions against disease transmission. For this purpose, although it was observed in our study that the preoperative HBsAg, anti-HBs, anti-HCV and anti-HIV seroprevalence were not higher than those in the population were, all health care workers should be trained in occupational diseases, vaccinated and followed up at regular intervals.Keywords: HBsAg; Anti-HCV; Anti-HIV; local anesthesia; dental surgery; seroprevalance; vaccine.